Socialization of the Use of Multimedia as a Learning Tool to Improve the Skills of MAS Darul Ilmi Students - Atika Aini Nasution; Baginda Harahap; Rohmah Alawiyah Harahap; Nasrul Wahdi; Zalikha (PT Inovasi Pratama Internasional, 2022)
Based on the observations that we found at MAS Darul Ilmi that the level of understanding and knowledge of multimedia was still low, so that's why the community service team provided socialization of the use of multimedia as a learning tool to improve the skills of class XI students at MAS Darul Ilmi Desa Haholongan. With the implementation of this service, a satisfactory result was obtained, that the students of MAS Darul Ilmi got information, insight, and knowledge that multimedia plays a very important role in learning, including that multimedia is very important for everyday life, especially at this time. Information and communication technology is advancing very rapidly